Complex anastomotic leaks following esophageal resections: the new stent over sponge (SOS) approach. Issue 6 (30th November 2012) - Gubler, C.; Schneider, P. M.; Bauerfeind, P.
Summary A new approach for the treatment of complicated anastomotic leaks following esophageal resections by combining vacuum‐assisted therapy with covered self‐expanding stents is reported. This is not an approach for a simple leak but a rescue maneuver for complex uncontained leaks. It is known that anastomotic leakages particularly situated in the chest can be successfully treated with endoscopically placed self‐expanding stents with/without additional drainage. If this approach fails, reoperation with substantial morbidity is frequently necessary. Two complicated anastomotic leakages refractory to stenting alone were successfully treated with the combination of an endo‐sponge‐assisted device covered by a self‐expanding metallic stent. If stent therapy fails or the perianastomotic abscess cavity is large and complex to drain from outside, the endoscopic two‐modality approach can be considered.